Neuraminidases 3 and 4 regulate neuronal function by catabolizing brain gangliosides. Issue 8 (19th September 2017) - Pan, Xuefang; De Britto Pará De Aragão, Camila; Velasco‐Martin, Juan P.; Priestman, David A.; Wu, Harry Y.; Takahashi, Kohta; Yamaguchi, Kazunori; Sturiale, Luisella; Garozzo, Domenico; Platt, Frances M.; Lamarche‐Vane, Nathalie; Morales, Carlos R.; et al.
ABSTRACT: Gangliosides (sialylated glycolipids) play an essential role in the CNS by regulating recognition and signaling in neurons. Metabolic blocks in processing and catabolism of gangliosides result in the development of severe neurologic disorders, including gangliosidoses manifesting with neurodegeneration and neuroinflammation. We demonstrate that 2 mammalian enzymes, neuraminidases 3 and 4, play important roles in catabolic processing of brain gangliosides by cleaving terminal sialic acid residues in their glycan chains. In neuraminidase 3 and 4 double‐knockout mice, GM3 ganglioside is stored in microglia, vascular pericytes, and neurons, causing micro‐ and astrogliosis, neuroinflammation, accumulation of lipofuscin bodies, and memory loss, whereas their cortical and hippocampal neurons have lower rate of neuritogenesis in vitro. Double‐knockout mice also have reduced levels of GM1 ganglioside and myelin in neuronal axons. Furthermore, neuraminidase 3 deficiency drastically increased storage of GM2 in the brain tissues of an asymptomatic mouse model of Tay‐Sachs disease, a severe human gangliosidosis, indicating that this enzyme is responsible for the metabolic bypass of β‐hexosaminidase A deficiency. Together, our results provide the first in vivo evidence that neuraminidases 3 and 4 have important roles in CNS function by catabolizing gangliosides and preventing their storage in lipofuscin bodies.—Pan, X., De Britto Pará De Aragão, C., Velasco‐Martin, J. P., Priestman, D. A., Wu, H. Y., Takahashi, K., Yamaguchi, K., Sturiale, L., Garozzo, D., Platt, F. M., Lamarche‐Vane, N., Morales, C. R., Miyagi, T., Pshezhetsky, A. V. Neuraminidases 3 and 4 regulate neuronal function by catabolizing brain gangliosides. FASEB J . 31, 3467–3483 (2017). www.fasebj.org